Impact of trauma system structure on injury outcomes: a systematic review protocol. Issue 1 (December 2017) - Moore, Lynne; Champion, Howard; O'Reilly, Gerard; Leppaniemi, Ari; Cameron, Peter; Palmer, Cameron; Abu-Zidan, Fikri; Gabbe, Belinda; Gaarder, Christine; Yanchar, Natalie; Stelfox, Henry; Coimbra, Raul; et al.
Abstract Background Injury represents one of the greatest public health challenges of our time with over 5 million deaths and 100 million people temporarily or permanently disabled every year worldwide. The effectiveness of trauma systems in decreasing injury mortality and morbidity has been well demonstrated. However, the organisation of trauma care varies significantly across trauma systems and we know little about which components of trauma systems contribute to their effectiveness. The objective of the study described in this protocol is to systematically review evidence of the impact of trauma system components on clinically significant outcomes including mortality, function and disability, quality of life, and resource utilization. Methods We will perform a systematic review of studies evaluating the association between at least one trauma system component (e.g. accreditation by a central agency, interfacility transfer agreements) and at least one injury outcome (e.g. mortality, disability, resource use). We will search MEDLINE, EMBASE, COCHRANE central, and BIOSIS/Web of Knowledge databases, thesis holdings, key injury organisation websites and conference proceedings for eligible studies. Pairs of independent reviewers will evaluate studies for eligibility and extract data from included articles. Methodological quality will be evaluated using elements of the ROBINS-I tool and the Cochrane risk of bias tool for non-randomized and randomized studies, respectively. Strength of evidence will be evaluated using the GRADE tool. Discussion We expect to advance knowledge on the components of trauma systems that contribute to their effectiveness. This may lead to recommendations on trauma system structure that will help policy-makers make informed decisions as to where resources should be focused. The review may also lead to specific recommendations for future research efforts. Systematic review registration This protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 28-06-2016. PROSPERO 2016:CRD42016041336 Available fromhttp://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42016041336 .